The temporal mechanics of the Fourth Gospel : a theory of hermeneutical relativity in the Gospel of John - Estes, Douglas. (Biblical Interpretation Series, 2008)
Spiritual but broken, theological but flawed-these are the words critics use to describe the Gospel of John. Compared to the Synoptics, John's version of the life of Jesus seems scrambled, especially in the area of time and chronology. But what if John's textual and temporal flaws have more to do with our implicit assumptions about time than a text that is truly flawed? This book responds to that question by reinventing narrative temporality in light of modern physics and applying this alternative temporal lens to the Fourth Gospel. From the singularity in the epic prologue to the narrative warping of event-like objects, this work explodes the elemental temporalities simmering below the surface of a spiritual yet superior Gospel text.